«Le Jurassique dans la partie orientale des zones externes des Cordilleres Bétiques». - Foucault, A.; Fourcade, E.; Paquet, J.; Azema, J.; Champetier, Y. (Cuadernos de Geología Ibérica, 1971)
Sin resumen